How to evaluate the postural balance in a more efficient and less expensive way? - Gilberto, Cuarelli [UNESP]; Alain, Di Donato; Julia, Misset; Adriana, Gomes Lisboa De Souza; Vania Cristina, Dos Reisa Miranda [UNESP]; José Elias, Tomazini [UNESP]; Guillaume, Thomann (Elsevier, 2018)
The assessment of postural control is important for the diagnosis and monitoring of balance disorder. Although there are qualitative and quantitative tools (Centre of pressure - CoP) for this evaluation. Some of them show limitations such as subjectivity or high equipment costs. The objective of this study is the preliminary validation of a more efficient and less expensive evaluation system with therapists. The method consists of finding similarities between CoP and CoM (Centre of Mass) during the evaluation of the postural balance with healthy people. Results: A user friendly human computer interface was developed, the low cost Microsoft Kinect V2 sensor was used to evaluate CoM and an unstable spring force platform was developed to evaluate CoP synchronously. For the comparison of data, a subject was evaluated under open eyes conditions in the unstable force platform. The test was performed using the user interface developed and the data collections showed evident similarities between CoP and CoM signals.
Keywords: Evaluation of postural balance; Force platform; Kinect Sensor; User-friendly measurement tool